Pengembangan E-LKPD Berbasis Project Terhadap Keterampilan Proses Sains Kelas IX SMP - Nabila Pujalola Pitaloka; Linna Fitriani; Yunita Wardianti (JURNAL PERSPEKTIF PENDIDIKAN, 2026)
This research is motivated by the problems reported by science teachers, namely the limited teaching materials for science learning, especially in biotechnology. Based on the results of the needs analysis questionnaire distribution, students reported that they study only from printed books and have not used additional teaching materials. Additional teaching materials are needed to support teachers and students in the form of E-LKPD. This study aims to determine the validity, practicality and effectiveness of the developed project-based E-LKPD. This type of research is development research (Research and Development) using a 4D development model. The instrument used to measure validity is a questionnaire with 3 expert assessments (media, material and language), practicality is measured using teacher and student response questionnaires, and effectiveness is measured using science process skills observation sheets. The results obtained, based on expert assessments, were 4.41 for media (very good category), 4.66 for material (very good category) and 4.41 for language (very good category). The results of teacher and student practicality showed an average of 93%, which is very practical. The results of the effectiveness of the science process skills indicators showed an average value of 83%, with very good criteria.